Measurements of flow and correlation phenomena in pp, pPb and PbPb collisions at CMS - Padula, Sandra S. [UNESP] (My University, 2016)
Many aspects of anisotropic collective flow in ultra relativistic heavy-ion collisions have been studied extensively in the past years using two or more particle correlations. An overview of collective flow and particle correlation measurements at CMS as a function of transverse momentum, pseudorapidity, event multiplicity, for both charged hadrons or identified particles will be presented. These results will be compared among pp, pPb and PbPb systems. Latest results of pp and PbPb data from 2015 run will also be discussed.